1999
DOI: 10.1002/(sici)1097-4636(19990615)45:4<277::aid-jbm1>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Transmission electron microscopic study of interface between bioactive bone cement and bone: Comparison of apatite and wollastonite containing glass-ceramic filler with hydroxyapatite and ?-tricalcium phosphate fillers

Abstract: We developed a bioactive bone cement that consists of apatite and wollastonite containing glass-ceramic (AW-GC) powder and bisphenol-a-glycidyl methacrylate (Bis-GMA) based resin. In this study, we made three types of cement (designated AWC, HAC, and TCPC) consisting of either AW-GC, hydroxyapatite (HA), or beta-tricalcium phosphate (beta-TCP) powder as the inorganic filler and Bis-GMA based resin as the organic matrix. These cements were implanted into rat tibiae and cured in situ. Specimens were prepared 1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 36 publications
2
18
0
Order By: Relevance
“…The results showed that an apatite layer was formed at the interface at 3 months. Contact of bone with an apatite layer for HA bioactive bone cement was also reported by Okada et al24 We observed that this apatite layer was transformed into mature bone after 6 months. Collagen fibers perpendicularly inserted into the Sr‐HA particles can strengthen and toughen the bone–Sr‐HA cement interface.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The results showed that an apatite layer was formed at the interface at 3 months. Contact of bone with an apatite layer for HA bioactive bone cement was also reported by Okada et al24 We observed that this apatite layer was transformed into mature bone after 6 months. Collagen fibers perpendicularly inserted into the Sr‐HA particles can strengthen and toughen the bone–Sr‐HA cement interface.…”
Section: Discussionsupporting
confidence: 84%
“…Neo et al23 found a mineralized collagen‐free layer on the surface of HA ceramic on and after the tenth day of implantation in rat tibiae. Later, Okada et al24 reported that HA particles were in contact with bone through an apatite layer in HA cement‐implanted rat tibiae. Recently, Fujita et al25 reported that an intervening layer was present on the surface of HA and a characteristic fibrillar structure was observed in the HA ceramic implanted between the parietal bone and the cranial periosteum of rats.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] Previously, the powders such as hydroxyapatite (HAp) and b-tricalcium phosphate (b-TCP), and cemented a-tricalcium phosphate (a-TCP) have been used for bone-filling materials in clinical use. [9][10][11] Although these materials are highly bioactive and biodegradable, figurations of these fillers have some problems. The powders are mechanically unstable and flow out to the surrounding tissue in prolonged use.…”
Section: Introductionmentioning
confidence: 99%
“…This is because it has high mechanical strength and good biocompatibility, as well as good chemical bonding to the bone surface through a calcium-phosphate-rich layer (Kitsugi et al 1987;Kokubo 1991). The new cement, used in this study contains Bis-GMA and bioactive glass powder and was developed (Kawanabe et al 1993) because polymethylmetacrylate cement, a fixing material in artificial joint replacement and traditionally used in orthopedics, has weak mechanical strength and produces a lot of heat during polymerization and does not directly make contact with the bone (Okada et al 1999a(Okada et al , 1999bFujita et al 2000). If a bioactive cement is used not only as a joining material between prosthesis and bone but also as a filling material for bone defects or as a bone supplement material for maxillary sinus floor augmentation to insert a dental implant, it is necessary to be able to mold the cement freely.…”
Section: Discussionmentioning
confidence: 99%
“…This is thought to be uncured BABC, especially the Bis-GMA, resulting from surrounding oxygen quenching the polymerization reaction by interacting with radicals produced by the benzoyl preoxide and N,N-dimethyl-p-toluidine (Okada et al 1999a(Okada et al , 1999bFujita et al 2000). At the surface of the BABC, AW-CG particles were in contact with bone through the crystal layer, which was about 0.4 mm thick 1 week after implantation, and consisted of calcium, phosphorus and a little silicon (Okada et al 1999a(Okada et al , 1999b. The mechanism behind this process has been studied by several researchers.…”
Section: Discussionmentioning
confidence: 99%